Association Between Heart Failure With Preserved Left Ventricular Ejection Fraction and Impaired Left Atrial Phasic Function in Hypertrophic Cardiomyopathy: Evaluation by Cardiac MRI Feature Tracking. Issue 1 (19th November 2021) - Shi, Rui; Shi, Ke; Huang, Shan; Li, Xiang; Xia, Chun‐Chao; Li, Yuan; He, Sen; Li, Zhen‐Lin; He, Yong; Guo, Ying‐Kun; Yang, Zhi‐Gang
Abstract : Background: The majority of heart failure (HF) in hypertrophic cardiomyopathy (HCM) manifests as a phenotype with preserved left ventricular (LV) ejection fraction; however, the exact contribution of left atrial (LA) phasic function to HF with preserved ejection fraction (HFpEF) in HCM remains unresolved. Purpose: To define the association between LA function and HFpEF in HCM patients using cardiac magnetic resonance imaging (MRI) feature tracking. Study Type: Retrospective. Population: One hundred and fifty‐four HCM patients (HFpEF vs. non‐HF: 55 [34 females] vs. 99 [43 females]). Field Strength/Sequence: 3.0 T/balanced steady‐state free precession. Assessment: LA reservoir function (reservoir strain [ ε s ], total ejection fraction [EF]), conduit function (conduit strain [ ε e ], passive EF), booster‐pump function (booster strain [ ε a ] and active EF), LA volume index, and LV global longitudinal strain (LV GLS) were evaluated in HCM patients. Statistical Tests: Chi‐square test, Student's t ‐test, Mann–Whitney U test, multivariate linear regression, logistic regression, and net reclassification analysis were used. Two‐sided P  < 0.05 was considered statistically significant. Results: No significant difference was found in LV GLS between the non‐HF and HFpEF group (−10.67 ± 3.14% vs. −10.14 ± 4.01%, P  = 0.397), whereas the HFpEF group had more severely impaired LA phasic strain ( ε s : 27.40 [22.60, 35.80] vs. 18.15 [11.98, 25.90]; ε e : 13.80 [9.20, 18.90] vs. 7.95 [4.30, 14.35]; ε a : 13.50 [9.90, 17.10] vs. 7.90 [5.40, 14.15]). LA total EF (37.91 [29.54, 47.94] vs. 47.49 [39.18, 55.01]), passive EF (14.70 [7.41, 21.49] vs. 18.07 [9.32, 24.78]), and active EF (27.19 [17.79, 36.60] vs. 36.64 [26.63, 42.71]) were all significantly decreased in HFpEF patients compared with non‐HF patients. LA reservoir ( β  = 0.90 [0.85, 0.96]), conduit ( β  = 0.93 [0.87, 0.99]), and booster ( β  = 0.86 [0.78, 0.95]) strain were independently associated with HFpEF in HCM patients. The model including reservoir strain (Net Reclassification Index [NRI]: 0.260) or booster strain (NRI: 0.325) improved the reclassification of HFpEF based on LV GLS and minimum left atrial volume index (LAVImin ). Data Conclusion: LA phasic function was severely impaired in HCM patients with HFpEF, whereas LV function was not further impaired compared with non‐HF patients. Level of Evidence: 4 Technical Efficacy: Stage 3